2015
DOI: 10.1016/j.ijnurstu.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Self-care confidence may be the key: A cross-sectional study on the association between cognition and self-care behaviors in adults with heart failure

Abstract: Cognition affects self-care behaviors indirectly, through self-care confidence. Interventions aimed at improving self-care confidence may improve self-care, even in heart failure patients with impaired cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 55 publications
4
67
1
4
Order By: Relevance
“…We found that lower self-care confidence was associated with all the self-care processes (maintenance, monitoring, and management), as others have found [15,20,21,41]. This is important because self-care confidence can be increased by improving patients' knowledge and skills through therapeutic education [42,43].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We found that lower self-care confidence was associated with all the self-care processes (maintenance, monitoring, and management), as others have found [15,20,21,41]. This is important because self-care confidence can be increased by improving patients' knowledge and skills through therapeutic education [42,43].…”
Section: Discussionsupporting
confidence: 70%
“…Self-care confidence is not self-care per se, but a factor strongly influencing self-care. Confidence is thought to underlie all self-care behaviours and mediate the relationship between factors such as cognition and self-care behaviours [16,17,21]. This theoretical approach acknowledges the dynamic nature and complexity of the self-care process.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, despite the studies that have been conducted on self-care in chronic illness, there is still a lack of knowledge and con- Vellone, et al, 2015) and caregiver self-care.…”
Section: Self-care Outcomes-caregiver-relatedmentioning
confidence: 99%
“…The caregiver sociodemographic characteristics of age, gender, marital status, and education level have been found to influence caregiver self‐care (Ågren, Evangelista, Hjelm, & Strömberg, ; Lee, Mudd, et al., ; Lee, Vellone, et al., ). In general, caregivers perform worse self‐care when they are older, male, patient's spouse, and better educated (Vellone et al., ). Caregiver burden may adversely alter the caregiver's life and reduce his or her contribution to patient self‐care (Dunbar et al., ; Wang, Sung, Yang, Chiang, & Perng, ).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics include lifestyle adjustment and risk factor control (exercise, diet control, substance use), controlling symptoms and disability, complex drug regimen optimization, coping with psychological and social demands, and effective coordination with the health care providers in follow-up and monitoring of physical indicators (6). Many studies have shown that people with better self-efficacy (7) are managing chronic illness optimally (8)(9). This paper aims to assess the perceived self-efficacy and its associations in selfmanaging chronic diseases among elderly patients in a clinic setting to provide insights into effective behaviour change programmes.…”
Section: Introductionmentioning
confidence: 99%